A Checklist for Sustainable Management of Archaeological Collections. Issue 1 (7th March 2017) - Childs, S. Terry; Benden, Danielle M.
ABSTRACT: The discipline of archaeology has been tolerating, at best, a "curation crisis" for decades that is unsustainable. The many issues related to long-term collections care continue to worsen. To counter this trend, we advocate that planning for collections be integrated into project administration from inception such that the management of archaeological collections begins before fieldwork and continues well after recovered collections reach the repository. To conceptualize this process, we identify the Collection Management Cycle as a framework for the many stakeholders involved in archaeological projects. We also provide a checklist that identifies the responsibilities stakeholders have to the collections they generate, fund, care for, manage, and/or study. Concerted use of the checklist and other proposed solutions will lead to a new era of a more sustainable archaeological practice. Abstract : Durante décadas, la disciplina de la arqueología ha tolerado, en el mejor de los casos, una "crisis de curación" que es insostenible. Los muchos problemas relacionados con el cuidado a largo plazo de las colecciones continúan empeorando. Para contrarrestar esta tendencia, proponemos que la planificación de las colecciones sea integrada en la administración del proyecto desde el comienzo, de tal forma que el manejo de las colecciones arqueológicas comience antes del trabajo de campo y continúe después de que las colecciones recuperadas lleguen al depósito. Para conceptualizar este proceso, identificamos el ciclo de administración de la colección como un marco para los muchos depositarios involucrados en los proyectos arqueológicos. Además, proveemos una lista de verificación que identifica las responsabilidades de los depositarios respecto a las colecciones que generan, financian, cuidan, gestionan y estudian. El uso conjunto de la lista de verificación y otras soluciones propuestas conducirá a una nueva era de prácticas arqueológicas más sostenibles.